West African agriculture and climate change: A comprehensive analysis - Jalloh, Abdulai; Nelson, Gerald C.; Thomas, Timothy S.; Zougmoré, Robert B.; Roy-Macauley, Harold (International Food Policy Research Institute, 2013)
This book examins the food security threats facing 11 of the countries that make up West Africa - Benin, Burkina Faso, Côte d'Ivoire, Ghana, Guinea, Liberia, Niger, Nigeria, Senegal, Sierra Leone, and Togo - and explores how climate change will increase the efforts needed to achieve sustainable food security throughout the region. West Africa's population is expected to grow at least through mid-century. The region will also see income growth. Both will put increased pressure on the natural resources needed to produce food, and climate change makes the challenges greater.